2013
DOI: 10.4081/ijas.2013.e17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benzo[a]pyrene on Gilthead Sea Bream (Sparus AurataL.) Hepatocytes Exposedin Vitroto Short and Long Term Trials

Abstract: In the present study, cytotoxic effects of the polycyclic aromatic hydrocarbons benzo [a] pyrene (B[a]P) were investigated in Sparus aurata hepatocytes primary cultures after acute and chronic exposure. Cells were treated with a wide range of B[a]P doses (1 pg/mL to 100 µg/mL) for 24, 48 and 72 h. B[a]P toxicity was quantified in sea bream hepatocytes by MTT assay and immunofluorescence analysis of apoptosis after the various exposure periods, in order to evaluate the hepatic damage and toxicity range. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Interestingly the EC50 for metabolic activity after exposure to BAP was 6 times lower than the EC50 for membrane integrity, which could indicate that BAP specifically target mitochondrial functions. This is supported by findings that exposure to BAP induced formation of reactive oxygen species (ROS) via CYP1A metabolism, resulting in harmful BAP diones which may cause cytotoxicity (full review see Verma et al, 2012) and potentially result in apoptosis (programmed cell death) at low concentrations and necrosis at high concentrations (Zacchino et al, 2013). No difference in the EC50 for metabolic activity and membrane integrity was observed after exposure to BPA in this study.…”
Section: Cell Viabilitysupporting
confidence: 73%
“…Interestingly the EC50 for metabolic activity after exposure to BAP was 6 times lower than the EC50 for membrane integrity, which could indicate that BAP specifically target mitochondrial functions. This is supported by findings that exposure to BAP induced formation of reactive oxygen species (ROS) via CYP1A metabolism, resulting in harmful BAP diones which may cause cytotoxicity (full review see Verma et al, 2012) and potentially result in apoptosis (programmed cell death) at low concentrations and necrosis at high concentrations (Zacchino et al, 2013). No difference in the EC50 for metabolic activity and membrane integrity was observed after exposure to BPA in this study.…”
Section: Cell Viabilitysupporting
confidence: 73%
“…We have previously shown by MTT assay that at lower doses of B[a]P, identified by increased cell viability, signs of apoptosis and cell damage in a high percentage of viable cells were reported (Zacchino et al, ). Additionally, we found that the cleaved caspase‐3 immunoreactivity was more frequently identified in proliferating oval cells than in non‐proliferating hepatocytes, suggesting an involvement in promoting transformation of oval cells, conceivably by allowing cells to evade the apoptotic process.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, we chose to restrict the genotoxicity investigation to the lowest doses of B[a]P, from 4 to 0.004 nM, which is the hypothetic genotoxic range as previously documented (Zacchino et al, ), to investigate the relation between apoptosis, inflammation, and cancer, by evaluating the genotoxic damage in combination with the cytotoxic assessment for a better understanding of the kind of response triggered by chronic exposure to the lowest B[a]P concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B a P at the lowest concentration caused toxic effects on the treated cells and its toxicity increased with increasing B a P concentration. Zacchino, Centoducati, Narracci, Selvaggi, and Santacroce () reported significant changes in the cultivated brain, liver, ovary, and kidney cells from Sparus aurata after 24‐h exposure to B a P. Several researchers have stated that prolonged exposure to higher concentration of toxicants leads to a reduction in the number of live cells and a decrease in cellular attachment to the culture plate, resulting in necrosis and cell death (Abdul Majeed et al, ; Rao, ; Weber & Janz, ). The prolonged exposure of the cell to contaminants leads to disturbance in the inhibition of free radicals produced by the contaminants within the cells.…”
Section: Discussionmentioning
confidence: 99%